(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Hand, foot, and mouth disease (HFMD) is an infectious disease caused by enterovirus (EV), easily transmitted and common in children. Objective: Evaluate the treatment outcomes of HFMD in children at Hau Giang Obstetrics and Pediatrics Hospital. Methods: A descriptive study using retrospective data was conducted on 131 pediatric patients diagnosed with HFMD according to the guidelines of the Vietnamese Ministry of Health and admitted for treatment at Hau Giang Obstetrics Pediatrics Hospital in 2023. Results: Male accounted for 54.2%, higher than female with 45.8%. The majority of children were in the age range of 36-60 months (25.2%). The most common reason for hospital admission was fever (66.4%), followed by rash, vesicles (45.8%), and mouth ulcers (43.5%). Symptoms such as vomiting (4.6%) and diarrhea (10.7%) had lower proportions. The majority of admitted patients were classified as HFMD grade 2a (64.1%), followed by grade 1 (21.4%) and grade 2b (12.2%). Most children were treated with Phenobarbital at a rate of 81.7%. Antibiotics were administered to 78.6% of children due to secondary infection, and 9.2% required oxygen therapy. The hospital stay duration ranged from 4-7 days. Conclusion: Most hospitalized children with HFMD were classified as grade 2a and 2b, the main treatment method was oral Phenobarbital, the hospital stay duration ranged from 4-7 days, and the majority had good recovery with few complications.